Análise da atuação dos atores no desenvolvimento do programa nacional de habitação rural no município de Cachoeira do Sul/RS - Atiyel, Carima Oliveira (2016)
There is a deficit in the housing sector in Brazil that affects both urban and rural area in the country. To reverse this unfavorable scenario, the federal government created in 2009 the Rural Housing Program (PNHR) that is part of a social policy that promotes access to housing to applicants for housing in rural areas and socioeconomic vulnerability condition. The rural housing deficit in the run-up to implementation of PNHR in 2008 was 916,478 housing units, after five years of operation of the Program, in 2014, 122,013 housing units were built in Brazil. This paper presents a study of the implementation of the Rural Housing Program in Cachoeira do Sul / RS, describing the historical aspects of housing in Brazil, the role of social actors in the construction of this policy, as well as major advances, barriers and results obtained from the advent of PNHR in the city.